Targeting of Mutant p53 and the Cellular Redox Balance by APR-246 as a Strategy for Efficient Cancer Therapy - Bykov, Vladimir J. N.; Zhang, Qiang; Zhang, Meiqiongzi; Ceder, Sophia; Abrahmsen, Lars; Wiman, Klas G. (Frontiers in Oncology, 2016)
TP53 is the most frequently mutated gene in cancer. The p53 protein activates transcription of genes that promote cell cycle arrest or apoptosis, or regulate cell metabolism and other processes . Missense mutations in TP53 abolish specific DNA binding of p53 and allow evasion of apoptosis and accelerated tumor progression. Mutant p53 often accumulates at high levels in tumor cells. Pharmacological reactivation of mutant p53 has emerged as a promising strategy for improved cancer therapy. Small molecules that restore wild type activity of mutant p53 have been identified using various approaches. One of these, APR-246, is a prodrug that is converted to the Michael acceptor methylene quinuclidinone (MQ) that binds covalently to cysteines in p53, leading to refolding and restoration of wild type p53 function. MQ also targets the cellular redox balance by inhibiting thioredoxin reductase (TrxR1) and depleting glutathione (GSH). This dual mechanism of action may account for the striking synergy between APR-246 and platinum compounds. APR-246 is the only mutant p53-targeting compound in clinical development. A phase I/IIa clinical trial in hematological malignancies and prostate cancer showed good safety profile and clinical effects in some patients. APR-246 is currently tested in a phase Ib/II trial in patients with high-grade serous (HGS) ovarian cancer.